TINJAUAN YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 76 TENTANG PENGUJIAN UNDANG-UNDANG NOMOR 17 TAHUN 2014 TENTANG MPR DPR DPD DAN DPRD TERHADAP UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - RAUF, MUHAMMAD AMIN; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Decision of the Constitutional Court Number 76 / PUU-XII / 2014 About Testing of Law Number 17 Year 2014 The People's Consultative Assembly, DPR, DPD, and DPRD are considered ultra petita and positive legislators, because the Constitutional Court in making this decision makes the rule of law new as well as making an unsolicited decision by the applicant.in Law Number 4 Year 2014 on the Second Amendment to Law Number 24 Year 2003 Article 45A and Article 57 has been regulated by the Constitutional Court in making the decision. Decision of the Constitutional Court Number 76 / PUU-XII / 2014 About Testing of Law Number 17 Year 2014 About MPR, DPR, DPD, and DPRD questioned its juridical validity ..the purpose of writing this skrripsi, namely: First, to know whether the decision of the Constitutional Court Number 76 / PUU-XII / 2014 About the Testing of Law Number 17 Year 2014 About the MPR, DPR, DPD and DPRD has been in accordance with the authority of the Constitutional Court as regulated in the law.secondly, to know the implications of the Constitutional Court's decision on examination, investigation and investigation, a member of the People's Legislative Assembly suspected of involvement in a crime after the issuance of the decision.The type of research used by the author, is the normative legal research is literature law research, because it makes the literature materials as the main pedestal.in this Normative legal research the authors do research on the principles of law and legal systematic starting from certain areas of law. The data sources used include Primary, Secondary, and Tertiary. Technique of collecting data by using literature study method.From the results of research problems there are two main things that can be concluded.first, Decision of the Constitutional Court Number 76 / PUU-XII / 2014 is considered as a decision of an ultra petita and positive legislator. Secondly, In the law, the authority of the Constitutional Court only cancels a norm of law if the law is not in accordance or contradictory to higher norms.the author's suggestion, Firstly, the Constitutional Court should perform its functions in accordance with those mandated by law.secondly, the Constitutional Court should have made a decision that is not contradictory or in accordance with the authority granted by law, if it is justified to make the ultra petita decision and positive legislator then it is necessary to amend the law of the Constitutional Court.Keywords: Testing of the Law, Constitutional Court, Ultra petita, Positive legislator